PELATIHAN INOVASI MODEL BISNIS DALAM MENINGKATKAN KINERJA UKM - Rodhiah; Jayanti, Yunia Arinda; Putri, Nadira Aulia (Transpublika Publisher, 2023)
Business model innovation (BMI) is considered a specialized form of innovation that helps improve business performance. The key to successfully improving business performance and competitiveness lies in the effective implementation of key managerial practices that lead to innovation. Businesses can innovate through products, processes and marketing strategies, and can innovate their business models. The objective of current service activity is to provide training to SMEs on business model innovation. The partner chosen to be the place of activity is engaged in the culinary business located in Jambi. The activity method of conducting online training through zoom meetings, presented in the form of PPT, about innovation, innovation fields, business model innovation, reasons for the importance of business model innovation, and strategies for implementing business model innovation has run smoothly. Training has been carried out according to the needs of partners assisted by two students as hosts. Partners were eager to receive the material presented by the PKM team. During the socialization process, the partners had many discussions and questions and answers with the PKM Team. The results of the activity can increase partner knowledge in an effort to improve business performance.